2018
DOI: 10.1103/physrevb.98.155123
|View full text |Cite
|
Sign up to set email alerts
|

Topological superconductivity in the Kondo-Kitaev model

Abstract: We investigate possible topological superconductivity in the Kondo-Kitaev model on the honeycomb lattice, where the Kitaev spin liquid is coupled to conduction electrons via the Kondo coupling. We use the self-consistent Abrikosov-fermion mean-field theory to map out the phase diagram. Upon increasing the Kondo coupling, a first order transition occurs from the decoupled phase of spin liquid and conduction electrons to a ferromagnetic topological superconductor of Class D with a single chiral Majorana edge mod… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
43
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(48 citation statements)
references
References 46 publications
3
43
1
Order By: Relevance
“…Similar to previous studies [6,[9][10][11][12][13][14][15], accommodation between the layers is observed in order to minimize the AA-stacking region, which proves especially significant for small twist angles. Buckling is found to occur for certain structures with twist angles that are below some critical buckling angle θ B , defined here as the angle below which negative modes are observed for the corresponding structure after one full CG relaxation.…”
supporting
confidence: 84%
See 2 more Smart Citations
“…Similar to previous studies [6,[9][10][11][12][13][14][15], accommodation between the layers is observed in order to minimize the AA-stacking region, which proves especially significant for small twist angles. Buckling is found to occur for certain structures with twist angles that are below some critical buckling angle θ B , defined here as the angle below which negative modes are observed for the corresponding structure after one full CG relaxation.…”
supporting
confidence: 84%
“…Unconventional superconductivity and magnetism were not typically associated with graphene until very recently with the observation of strong electronic correlation in bilayer graphene twisted roughly at the θ = 1.1°magic angle [1][2][3][4][5]. This effect is related to the emergence of flat electronic bands with narrow band width [1,[5][6][7][8], and theoretical studies have established the importance of structural relaxation in the description of these phenomena [6,[9][10][11][12][13][14][15]. The atomic relaxation in twisted bilayer graphene (tBLG) is linked to the development of strain fields that tend to minimize the unfavorable AA-stacking regionswith local buckling-and lead to the formation of triangular domain patterns in the moiré pattern.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Several groups have reported the experimental observation of correlated insulator states in both doped and undoped tBLG near the magic twist angle [1][2][3][4]. Despite much theoretical work, no consensus has yet been reached regarding the microscopic mechanism of these phases [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]. Superconductivity is also found at low temperatures [2][3][4], but neither the nature of the pairing interaction nor the symmetry of the superconducting order parameter have been determined.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent studies, using perturbative scaling [13,14] as well as more rigorous numerical treatment using the numerical renormalization group [15], have shown the existence of an unstable fixed point that gives rise to a first-order flux transition between the weak-coupling flux-free phase and the strongcoupling impurity-flux phase, upon tuning the coupling between the impurity and the lattice. Other studies have used slave-particle mean field theories to investigate situations involving a Kondo lattice model on the honeycomb lattice with Kitaev interactions among the local moments, giving rise to fractionalized Fermi liquid behavior and exotic superconductivity [16,17]. Here, the effective hybridization of Majorana modes and conduction electrons due to the Kondo effect imprints superconductivity onto the conduction electron system.…”
Section: Introductionmentioning
confidence: 99%